Transitivity in health utility measurement: An experimental analysis - Ulrich Schmidt; Michael Stolpe (Health Economics Review, 2011)
Several experimental studies have observed substantial violations of transitivity for decisions between risky lotteries over monetary outcomes. The goal of our experiment is to test whether these violations also affect the evaluation of health states. A particular feature of our experimental design is that it takes into account the possible role of decision errors for generating violations of transitivity. Since we find neither substantial nor systematic deviations from transitive choice behaviour, we can conclude that previously reported violations do not seem to bias health utility measurement.
Keywords: 330; transitivity; health utility; errors